A new insight on the thermal resistance source of diamond -SiC interface: Based on non-equilibrium molecular dynamics - Kunlong Zhao; Huagang Lyu; Biao Wang; Zhijie Ye; Wenxin Cao; Dongmeng Shi; Xiaobin Hao; Sen Zhang; Zhuochao Wang; Xiaolei Wang; Xingchun Xu; Jiaqi Zhu (Journal of Materials Research and Technology)
Diamond/silicon carbide (diamond/SiC) is the future development of thermal management materials for it's high thermal conductivity, and interface research is the key to improve the performance of diamond/SiC. In this paper, we focus on the transition layer SixC(1-x) between diamond and SiC for the first time, and investigate its influence on heat transfer properties by using non-equilibrium molecular dynamics simulations. The source of interfacial thermal resistance (ITR) of the transition layer is analyzed through phonon density of states and phonon group velocity. The results show that the presence of 5 nm SixC(1-x) transition layer leads to the ITR of 2.96 × 10−9 m2K/W between diamond and SiC, and with the increase of transition layer thickness, the ITR can reach up to 4.29 × 10−9 m2K/W. The range of ITR is significantly higher than the traditionally accepted value of 6 × 10−10 m2K/W. The influence of atom doping mode and lattice constant on the ITR range is relatively limited, whereas the impact of atom distribution mode more significant. Based on the phonon group velocity analysis, it is evident that the disordered distribution of silicon atoms in Si0.2C0.8 significantly reduces the thermal conductivity of the transition layer. This disordered distribution is also the main source of ITR. This study provides a new insight into the origin of ITR between diamond and SiC, offering a reference for the interfacial engineering design of high-thermal conductivity diamond/SiC composites.